Sequential liver and kidney transplantation from a single living donor in two young adults with primary hyperoxaluria type 1. Issue 6 (28th May 2013) - Mor, Eytan; Nesher, Eviatar; Ben‐Ari, Ziv; Weissman, Irit; Shaharabani, Ezra; Eizner, Sigal; Solomonov, Evegny; Rahamimov, Ruth; Braun, Marius
<x xml:space="preserve">Abstract</x> Using living donor organs for sequential liver and kidney transplantation (SeqLKT) in patients with primary hyperoxaluria type 1 (PH1) has emerged as a viable approach. Taking both organs from a single donor, however, is rare. There are 8 reported cases of SeqLKT in the literature, and in all but 1 case, children were the recipients. We present our experience with SeqLKT in 2 young adults with PH1. In the first case, with an interval between procedures of 4.5 months, SeqLKT was performed with a right liver lobe from a 47‐year‐old father for his 19‐year‐old son with PH1 who was on dialysis for 2 years before transplantation. Both the donor and the recipient had an uneventful recovery, although there was re‐exploration for the control of bleeding in the recipient after liver transplantation. Thirty‐three months after transplantation, the patient had normal liver and renal function. In the second case, with an interval between procedures of 22 days, SeqLKT was performed with organs from a 45‐year‐old father for his 19‐year‐old daughter with PH1 who was on dialysis for 8 months. The recipient procedures, including right liver lobe transplantation and kidney transplantation, were uneventful. The donor underwent percutaneous drainage of a subphrenic collection and subsequently fully recovered. Eighteen months after transplantation, the recipient's liver and renal allograft function was normal. In conclusion, because of the severe organ shortage, living related SeqLKT using the same donor should be carefully considered for young adults with PH1. Liver Transpl 19:646–648, 2013. © 2013 AASLD.